The Future of AI in Healthcare: A Survey of Medical Professors’ Opinions - Montazerian, Sara; Mehdipour, Yousef (AI and Tech in Behavioral and Social Sciences, 2025)
Nowadays, the use of artificial intelligence (AI) in medical sciences has been growing significantly, impacting diagnosis, care, and treatment of diseases. AI systems also serve as clinical assistants. Given that all healthcare professionals begin their education at universities, the aim of this research was to assess the awareness and attitudes of medical university professors toward incorporating an AI course in medical sciences. This descriptive-analytical study was conducted during 2024 at Torbat Heydarieh University of Medical Sciences. The study population included all faculty members, both academic and non-academic, totaling 152 participants. Data were collected using a composite questionnaire covering four dimensions: familiarity, awareness, willingness to learn, and professors’ perspectives on AI. The validity of the questionnaire was confirmed, and its reliability was established with a Cronbach’s alpha coefficient of 73%. Data were analyzed using SPSS version 26. In this study, significant correlations were found between familiarity, awareness, willingness to learn, and professors’ perspectives regarding AI, as well as their gender, age, and work experience. Professors with 11-20 years of work experience demonstrated greater familiarity compared to their counterparts. However, younger professors with less than 10 years of experience had higher levels of awareness. The willingness to learn about AI was consistent across all levels of work experience. Professors expressed positive views on integrating AI into medical practice and adding it to the curriculum. Based on the findings of this study, incorporating an AI course into the medical curriculum for students can contribute to modern medical advancements and enhance the efficiency of healthcare delivery. Additionally, organizing AI training workshops for professors would be beneficial in this regard.